Rhodanese Functions as Sulfur Supplier for Key Enzymes in Sulfur Energy Metabolism - Aussignargues, Clément (American Society for Biochemistry and Molecular Biology, 2012)
How microorganisms obtain energy is a challenging topic, and there have been numerous studies on the mechanisms involved. Here, we focus on the energy substrate traffic in the hyperthermophilic bacterium Aquifex aeolicus. This bacterium can use insoluble sulfur as an energy substrate and has an intricate sulfur energy metabolism involving several sulfur-reducing and -oxidizing supercomplexes and enzymes. We demonstrate that the cytoplasmic rhodanese SbdP participates in this sulfur energy metabolism. Rhodaneses are a widespread family of proteins known to transfer sulfur atoms. We show that SbdP has also some unusual characteristics compared with other rhodaneses; it can load a long sulfur chain, and it can interact with more than one partner. Its partners (sulfur reductase and sulfur oxygenase reductase) are key enzymes of the sulfur energy metabolism of A. aeolicus and share the capacity to use long sulfur chains as substrate. We demonstrate a positive effect of SbdP, once loaded with sulfur chains, on sulfur reductase activity, most likely by optimizing substrate uptake. Taken together, these results lead us to propose a physiological role for SbdP as a carrier and sulfur chain donor to these key enzymes, therefore enabling channeling of sulfur substrate in the cell as well as greater efficiency of the sulfur energy metabolism of A. aeolicus.